1971
DOI: 10.1073/pnas.68.2.312
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Converging Metabolic Pathways: Activation of the Cystathionine γ-Synthase of Neurospora crassa by Methyltetrahydrofolate

Abstract: Methyltetrahydrofolate synchronizes the activities of the two branches of the pathway of methionine biosynthesis in Neurospora crassa by serving as an essential activator of cystathionine -y-synthase and antagonizing the feedback inhibition of this enzyme by S-adenosylmethionine. Activation is specific for the methylated form of folate and increases with increasing glutamate content. The inability of extracts of me-i and me-6 mutants to form cystathionine that has been previously reported is due to the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1971
1971
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…1) (Paszewski and Grabski, 1975), but its status has now been revised. In this regard it is worth noting that a N. crassa met-1 mutant (impaired in MTHFR) also showed no CGS activity due to a lack of CH 3 -THF (Selhub et al, 1971). Polyglutamylated forms of methyltetrahydrofolate serve as essential activators of CGS and synchronize the two converging metabolic pathways leading to methionine formation in N. crassa.…”
Section: Discussionmentioning
confidence: 98%
“…1) (Paszewski and Grabski, 1975), but its status has now been revised. In this regard it is worth noting that a N. crassa met-1 mutant (impaired in MTHFR) also showed no CGS activity due to a lack of CH 3 -THF (Selhub et al, 1971). Polyglutamylated forms of methyltetrahydrofolate serve as essential activators of CGS and synchronize the two converging metabolic pathways leading to methionine formation in N. crassa.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, we analyzed the effect of AdoMet and 5-methyl-THF, alone or in combination, on both versions of the enzyme. These metabolites were of particular interest because Selhub et al (1971) have shown that, in Neurospora crassa, 5-methyl-THF acts as an essential activator of CGS and antagonizes the feedback inhibition of the enzyme by AdoMet. Also, plant and Neurospora CGSs share a common feature as they possess an N-terminal extension of about 180 to 200 residues that is not found in bacterial CGS.…”
Section: Discussionmentioning
confidence: 99%
“…and a heterologous protein (i.e., MS) is not unprecedented: 5-methyltetrahdrofolate is an activator of cystathionine ␥-synthase in Neurospora crassa (40), an inhibitor of glycine methyltransferase in mammalian systems (41), and binds to cytosolic serine hydroxymethylase (42). Binding to serine hydroxymethylase is associated with diminished synthesis of methionine and diversion of the flow of one carbon units toward thymidylate synthesis.…”
Section: Discussionmentioning
confidence: 99%